Authors' reply: the problem of the poor control arm in surgical randomized controlled trials (Br J Surg 2013; 100: 172-173) - Strobel, Oliver; Büchler, Markus W. (The British journal of surgery, 2013)
SirWe thank Mr Smart for his comments. The intention of our article was, however, to increase awareness of how poor results in the control arm of surgical randomized clinical trials (RCTs) can occur, consequently resulting in the apparent superiority of the novel treatment, a problem that is not immediately obvious to everybody, as it is to Mr Smart or the ingenious Captain Jean Luc Picard. Since Horton's polemic1, there has been a steady increase in the number of surgical RCTs, which are considered to provide the highest level of evidence, although some are of poor quality. We wanted to emphasize that RCTs cannot be viewed in isolation but only in the context of contemporary literature. This literature may include other RCTs, registries and observational trials - each method with its own limitations1.